Glyphosate resistance in Ambrosia trifida: Part 2. Rapid response physiology and non‐target‐site resistance. Issue 5 (2nd May 2017) - Moretti, Marcelo L; Van Horn, Christopher R; Robertson, Renae; Segobye, Kabelo; Weller, Stephen C; Young, Bryan G; Johnson, William G; Douglas Sammons, R; Wang, Dafu; Ge, Xia; d' Avignon, André; Gaines, Todd A; et al.
Abstract: BACKGROUND: The glyphosate‐resistant rapid response (GR RR) resistance mechanism in Ambrosia trifida is not due to target‐site resistance (TSR) mechanisms. This study explores the physiology of the rapid response and the possibility of reduced translocation and vacuolar sequestration as non‐target‐site resistance (NTSR) mechanisms. RESULTS: GR RR leaf discs accumulated hydrogen peroxide within minutes of glyphosate exposure, but only in mature leaf tissue. The rapid response required energy either as light or exogenous sucrose. The combination of phenylalanine and tyrosine inhibited the rapid response in a dose‐dependent manner. Reduced glyphosate translocation was observed in GR RR, but only when associated with tissue death caused by the rapid response. Nuclear magnetic resonance studies indicated that glyphosate enters the cytoplasm and reaches chloroplasts, and it is not moved into the vacuole of GR RR, GR non‐rapid response or glyphosate‐susceptible A. trifida . CONCLUSION: The GR RR mechanism of resistance is not associated with vacuole sequestration of glyphosate, and the observed reduced translocation is likely a consequence of rapid tissue death. Rapid cell death was inhibited by exogenous application of aromatic amino acids phenylalanine and tyrosine. The mechanism by which these amino acids inhibit rapid cell death in the GR RR phenotype remains unknown, and it could involve glyphosate phytotoxicity or other agents generating reactive oxygen species. Implications of these findings are discussed. The GR RR mechanism is distinct from the currently described glyphosate TSR or NTSR mechanisms in other species. © 2017 Society of Chemical Industry Abstract : This study explores the physiology of the rapid response and the possibility of reduced translocation and vacuolar sequestration as non‐target‐site resistance (NTSR) mechanisms.